Reconstructing Industrial Forest Spatial Planning Policy for Ecological Mitigation and Global Environmental Justice - Febrian Chandra; Hartati Hartati; Helmi Helmi; Muhammad Reza Halomoan (Journal of Law and Legal Reform, 2026)
The spatial planning of Industrial Forest Plantations (HTI) in Indonesia faces increasing challenges as economic expansion frequently generates ecological degradation and disaster risks. This article examines the need to reconstruct legal policies governing HTI spatial planning to integrate disaster-mitigation and ecological-justice principles. Using normative legal research with statutory, conceptual, and comparative approaches, this study analyzes Law No. 6 of 2023 and related forestry regulations, supported by empirical environmental data from the WALHI Environmental Outlook (2025) and KSDAE reports. The findings reveal that the current spatial planning framework facilitates what can be described as “legal deforestation,” where forest exploitation significantly exceeds the state’s ecological recovery capacity. This imbalance contributes to increasing hydrological disasters and socio-ecological injustices affecting local and indigenous communities. Comparative insights from Nordic forestry governance highlight the importance of transparent geospatial monitoring and balanced forest management. This article proposes a legal reconstruction model that integrates the Rights of Nature, ecological disaster risk insurance, and stronger supremacy of spatial planning. Such reforms are essential to align Indonesia’s forestry governance with global environmental standards and to ensure intergenerational ecological justice.